Kinerja Keuangan pada PT Garuda Indonesia (Persero) Tbk Periode 2013-2017 - Yolla Haja Olyvia; Rindang Matoati (Jurnal Manajemen dan Organisasi, 2019)
The growth of the national aviation industry has been quite rapidly in last view times. Along with this condition, there are only few of airline companies are able to survive, which are supported by strong financial conditions and good corporate management. PT Garuda Indonesia (Persero) Tbk a flag carrier that is able to maintains its existence until now. This study aims to analyze the financial performance of PT Garuda Indonesia (Persero) Tbk for the period of 2013-2017 using financial ratio analysis based on minister of BUMN decree number: KEP-100 / MBU / 2002, trend analysis and analysis of the potential bankruptcy of the Altman’s Z-Score model. The data analysis method used in this study was descriptive quantitative. Data processing was performed using Microsoft Excel 2013 and Minitab 17 software. The results of the study indicate financial performance of PT Garuda Indonesia (Persero) Tbk for the period 2013-2017 tends to decrease and the value of Z-Score obtained has great potential for bankruptcy.